Chromosome-level genome assembly of starry flounder (Platichthys stellatus) - Weiwei Zheng; Changlin Liu; Shenglei Han; Tengteng Wang; Tao Yang; Zhihong Liu; Dong Xu; Huizong Han; Xiaoqing Xi; Changwei Shao; Kaiqiang Liu (Scientific Data)
Abstract Starry flounder (Platichthys stellatus) is widely distributed along the coastlines of the North Pacific. As an euryhaline flatfish, it can adapt to a wide range of environmental salinity ranging from freshwater to seawater, and is a promising aquaculture flatfish species in Korea and North China. However, no high-quality starry flounder reference genome has been reported to date, which greatly limits the studies of genetics and functional genomics. Here, we obtained a high-quality chromosome-level starry flounder genome assembly with a length of 643.56 Mb (scaffold N50: 26.19 Mb, contig N50: 10.00 Mb) combining short-reads sequencing, PacBio HiFi sequencing, and Hi-C sequencing. Approximately 94.02% of assembled sequences were anchored into 24 pseudochromosomes, and a total of 18 telomeres were detected. Totally 22,835 protein-coding genes and 227.87 Mb repetitive sequences were identified. In summary, the high-quality chromosome-level genome assembly not only provides valuable resources for genetic research in starry flounder, but also advances the development of molecular breeding technology of starry flounder.